Aspects of aerobic endurance in middle school students - Gyulla KÖRMENDI; Simona LUCACIU; Gheorghe LUCACIU (Editura Universităţii din Oradea, 2022)
The general, harmonious physical development of school youth is a major desideratum included among the aims of physical education promoted by all authors with concerns in this field, being the most important requirement of the ideal of physical education, a presence in any stage of design, planning, organization and development. this activity. In accordance with this task of great importance for school physical education, we mention that this paper aims primarily at the student, but also to improve the activities of teachers in the direction of achieving higher levels, a very important goal in general physical training of students and mainly the development / optimization of aerobic endurance. Goal: the role of this paper is to highlight the effects that "application paths" can generate as means oriented towards the development of aerobic endurance. Methods: In carrying out the research we mainly used the field test method, the observation method and the statistical-mathematical method. Results: The means used in the form of "application path" influence and demand at the same time the cardiovascular and respiratory systems and automatically lead to the increase of somato-functional indices of students.